Critical Discourse of the Van Dijk Model on Roasting Marshel Widiyanto in the Mata Najwa Program Youth in Power Episode - Rojudin Rojudin; Intan Sari Ramdhani (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study discusses Marshel Widianto's roasting video broadcast on Najwa Shihab's Youtube media with the title "Young Power: What Happens If Young People Have Power". The purpose of this study is to analyze the elements of discourse using the Teun A. Van Dijk model on Marshel Widianto's roasting show that aired on Najwa Shihab's Youtube media with the title "Young Power: What Happens If Young People Have Power". The research method used in this research was descriptive qualitative. The data analysis technique used by the researcher was using content analysis. The technique used in data collection is the note-taking technique. Based on the results of the study, it can be concluded that there are four different elements. Among them are semantic elements (background, details, intent) which discuss in detail the meaning to be conveyed in a discourse. Furthermore, the syntactic elements (sentence forms, pronouns, stylistics, and rhetorical) these four elements are used to analyze the form or sentence structure used by Marshel Widianto and the researchers found an emphasis made by using the inclusion of pictures, word order in the title, letter thickening. , the use of capital letters, colons and so on on the cover (clickbait) of videos that air on Najwa Shihab's youtube channel. The results of the analysis that have been carried out by researchers are of course different from other videos that appear on YouTube, this is due to ideological differences, the message to be conveyed in the discourse, packaging in a video and so on.Keywords: Youtube, Teun Van. Dijk, Critical discourse analysis, Marshel Widianto.